The contribution of information findability attributes to serendipity in information environments: conceptual relationships - Trindade, Alessandra Stefane Candido Elias da; Sanchez, Fernanda Alves [UNESP] (Univ Federal Santa Catarina, 2024)
Objective: To :To describe how information environments can enhance serendipity through information findability attributes. Method: Theoretical research, with a descriptive objective, uses a qualitative approach and bibliographic research, conducted in the Web of Science (WoS) and the Brazilian Database in Information Science (BRAPCI). Results :Different environmental aspects favor informational serendipity, namely, variety of content; personalizing access to information; leading to the unexpected; stimulating curiosity and serendipity; encouraging exploration and navigation; unobstructed access. These general principles can be achieved through the attributes of information findability and elements of the environment Conclusions: It is suggested that future studies addressing serendipity from the perspective of information discovery use the terms 'infoserendipity' or 'informational serendipity' and that the general principles presented can be used as a guide to evaluate the capacity of information environments to promote serendipitous experiences.
Keywords: Information environments; Information findability; Information Findability Attributes; Information discovery; Serendipity